Large-Angle Electron Diffraction Structure in Laser-Induced Rescattering from Rare Gases - Ray, D.; Ulrich, B.; Bocharova, I.; Maharjan, C.; Ranitovic, P.; Gramkow, B.; Magrakvelidze, M.; De, S.; Litvinyuk, I. V.; Le, A. T.; Morishita, T.; Lin, C. D.; et al. (My University, 2008)
We have measured full momentum images of electrons rescattered from Xe, Kr, and Ar following the liberation of the electrons from these atoms by short, intense laser pulses. At high momenta the spectra show angular structure (diffraction) which is very target dependent and in good agreement with calculated differential cross sections for the scattering of free electrons from the corresponding ionic cores.